2005
DOI: 10.1136/sti.2004.009423
|View full text |Cite
|
Sign up to set email alerts
|

Screening injecting drug users for sexually transmitted infections and blood borne viruses using street outreach and self collected sampling

Abstract: Background: Injecting drug users (IDUs) are a marginalised population, who infrequently access health services for screening for sexually transmitted infections (STIs) and blood borne viruses (BBVs), and are at high risk of these infections. Objectives: To use street outreach and self collection of samples for STI screening, to establish the prevalence of BBVs and STIs, and to identify risk behaviours among a group of culturally diverse street based IDUs. Methods: This was a cross sectional study of 314 IDUs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 31 publications
1
46
1
1
Order By: Relevance
“…The Hepatitis C European Network for C-operative Research (HENCORE) group had reported the prevalence of 80% hepatitis C among intravenous drug users (IVDU) (Touzet et al, 2000). There was 36.6% positivity of hepatitis C in the intravenous drug users in Sydney, Australia and 74% hepatitis C positivity in the intravenous drug users in Melbourne, Australia (Bradshaw et al, 2005;Maher et al, 2004). In the recent study in London, England, the 428 intravenous drug users were under the age of 30 having 44% antibodies to hepatitis C compared to 4% with HIV, this is the incidence of 41.8 cases per 100 persons (Judd et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The Hepatitis C European Network for C-operative Research (HENCORE) group had reported the prevalence of 80% hepatitis C among intravenous drug users (IVDU) (Touzet et al, 2000). There was 36.6% positivity of hepatitis C in the intravenous drug users in Sydney, Australia and 74% hepatitis C positivity in the intravenous drug users in Melbourne, Australia (Bradshaw et al, 2005;Maher et al, 2004). In the recent study in London, England, the 428 intravenous drug users were under the age of 30 having 44% antibodies to hepatitis C compared to 4% with HIV, this is the incidence of 41.8 cases per 100 persons (Judd et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The use of psycho-active substances can make drug addicts less aware of or concerned about STDs (15) . In one randomized study, the prevalence of HCV antibodies was significantly (p≤0.001)…”
Section: Discussionmentioning
confidence: 99%
“…Studies among IDUs generally show a moderate prevalence of STIs, similar to that observed in the general population [13,14] . For example, a recent study carried out in Baltimore among IDUs aged under 30 years showed the prevalence of Chlamydia trachomatis and Neisseria gonorrhoeae to be 4 and 1.2%, respectively, and the prevalence of those infections from a population-based study was 3.0 and 5.3%, respectively [15] .…”
Section: Introductionmentioning
confidence: 88%